Impact of E-Commerce in Industry - A Rizaldi; Z Madany (International Journal of Research and Applied Technology (INJURATECH), 2021)
E-Commerce is a buying and selling activity, where the activities of sellers and buyers are carried out through the internet. This study aims to illustrate the impact of using E-Commerce, especially for the benefits of E-Commerce for business strategies. There are several ways to develop business both manually and computers. But in this era of the global economy, not only is the work process computerized, but the sales process also utilizes these facilities. The goal is to use e-commerce to attract more consumers because it can reach wider consumers. This research uses descriptive qualitative method and literature study based on previous research. So is it enough to make E-Commerce an industry that will experience an increase in sales results? Of course not, but the more quality E-Commerce that is created will further increase profits for the company